Eugenol Improves Follicular Survival and Development During in vitro Culture of Goat Ovarian Tissue - Silva, R. F.; Lima, L. F.; Ferreira, Anna C. A.; Silva, A. F. B.; Alves, D. R.; Alves, B. G.; Oliveira, A. C.; Morais, Selene M.; Rodrigues, Ana Paula R.; Santos, Regiane R.; Figueiredo, J. R. (Frontiers in Veterinary Science, 2022)
This study evaluated the effects of different concentrations (10, 20, or 40 μM) of eugenol (EUG 10, EUG 20, or EUG 40), ascorbic acid (50 μg/mL; AA) or anethole (300 μg/mL; ANE 300) on the in-vitro survival and development of goat preantral follicles and oxidative stress in the cultured ovarian tissue. Ovarian fragments from five goats were cultured for 1 or 7 days in Alpha Minimum Essential Medium (α-MEM+) supplemented or not with AA, ANE 300, EUG 10, EUG 20 or EUG 40. On day 7 of culture, when compared to MEM, the addition of EUG 40 had increased the rate of follicular development, as observed by a decrease in the proportion of primordial follicles alongside with an increase in the rate of normally developing follicles. Furthermore, EUG 40 significantly increased both follicular and oocyte diameters. Subsequently, ovarian fragments from three goats were cultured for 1 or 7 days in α-MEM+ supplemented or not with AA, ANE 300 or EUG 40. All tested antioxidants, except ANE 300, were able to significantly decrease the levels of reactive oxygen species in the ovarian tissue, but EUG 40 could most efficiently neutralize free radicals. All ovarian tissues cultured in the presence of antioxidants, especially EUG 40, presented a significant decrease in H3K4me3 labeling, indicating a silencing of genes that play a role in the inhibition of follicular activation and apoptosis induction. When compared to cultured control tissues, both EUG 40 and ANE 300 significantly increased the intensity of calreticulin labeling in growing follicles. The mRNA relative expression of ERP29 and KDM3A was significantly increased when the culture medium was supplemented with EUG 40, indicating a response to ER stress experienced during culture. In conclusion, EUG 40 improved in-vitro follicle survival, activation and development and decreased ROS production, ER stress and histone lysine methylation in goat ovarian tissue.